Pneumonia and concurrent eggs retention in a river terrapin (Batagur baska) - Che Ishak, Inirah; Che' Amat, Azlan; Teoh, H. X.; Yawah, Donny; Abdullah, Faez Firdaus Jesse (Veterinary Association Malaysia, 2017)
A case report of pneumonia and egg retention in a river terrapin was presented in this paper. A 20 year-old river terrapin (Batagur baska) was presented with complaint of coughing with blood discharge, wheezing breathing and inappetance. Plain radiograph showed both right and left lung lobes were consolidated due to pneumonia 90% and 70%, respectively. Tentative diagnosis of pneumonia due to opportunistic bacterial infection of Chromobacterium sp. and Plesiomonas shigelloides was made in this case based on bacterial isolation and response to antibiotic and anti-inflammatory drugs. Enrofloxacin and flunixin meglumine were administered from Day-1 to -5. Enrofloxacin was then changed to gentamicin since it showed resistance in those bacteria. No clinical changes were observed. Gentamicin was given at rate 2.5 mg/kg once a week intramuscularly and prednisolone 2 mg/kg once on Day-6 given intramuscularly, showed a response on Day-10 of hospitalisation with the evidence of reduction in lung consolidation by almost 90% clear of lung lobes from pneumonia. Sixteen thin-shelled eggs were also observed in the coelomic cavity on radiographic images. Active laying season, prolonged laying period and the history of laying only two eggs a week before presenting to hospital gives a highly suggestive diagnosis of egg retention syndrome. To encourage laying, the terrapin was given a daily parenteral calcium supplement, oxytocin 5 IU/kg intramuscularly (Day-10 hospitalisation) and was released for sunbath and to sand twice daily. The eggs were completely laid on Day-11 and the overall terrapin condition was greatly improved 2 weeks post-hospitalisation.